If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -37 = 5(y + -9) Reorder the terms: -37 + 9y = 5(y + -9) Reorder the terms: -37 + 9y = 5(-9 + y) -37 + 9y = (-9 * 5 + y * 5) -37 + 9y = (-45 + 5y) Solving -37 + 9y = -45 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -37 + 9y + -5y = -45 + 5y + -5y Combine like terms: 9y + -5y = 4y -37 + 4y = -45 + 5y + -5y Combine like terms: 5y + -5y = 0 -37 + 4y = -45 + 0 -37 + 4y = -45 Add '37' to each side of the equation. -37 + 37 + 4y = -45 + 37 Combine like terms: -37 + 37 = 0 0 + 4y = -45 + 37 4y = -45 + 37 Combine like terms: -45 + 37 = -8 4y = -8 Divide each side by '4'. y = -2 Simplifying y = -2
| 4x+9x-8x-5x=15 | | y=11+-5x | | 3(x-6)=39 | | 8-(6-6n)+9n=-2+12(n+1) | | (m^2+6m+4)(3m-1)=0 | | 9y^2+2+16=-24y | | 2x+6-x=(3x+18) | | 9y^22+16=-24y | | (w-9)*(w+4)= | | (5x-4)=(4x-7+1) | | =x+3-15+8x | | 7x^3+7x^2+7x+2=0 | | 32x^2-332x+8=0 | | 6x+8=4(x+9) | | 22=t+17 | | 9x+8x-7x-5x=65 | | 3a=a+26+12 | | 2.5s+2.5=7.5 | | 2.5s+2.4=7.5 | | x(2)+40=180 | | 2(2-j)=(j+10) | | 2(1-x)=6 | | 25=2x-y | | 4x+(2x+18)=180 | | 2x^2-4x-3=27 | | 2d=24+6d | | 8+5(z-4)=2(z+7) | | 7(3-x)=14 | | Py+aye=-4y+8 | | 3v-7v=5 | | 3x^2+23x-8.5=0 | | 8v-6v=4 |